CHEMICAL AND ISOTOPIC FRACTIONATIONS BY EVAPORATION AND THEIR COSMOCHEMICAL IMPLICATIONS - Ozawa K.; Nagahara H. (My University, 2001)
A kinetic model for evaporation of a multi-component condensed phase with a fixed rate constant of the reaction is developed. A binary system with two isotopes for one of the components undergoing simple thermal histories (e.g., isothermal heating) is investigated in order to evaluate the extent of isotopic and chemical fractionations during evaporation. Diffusion in the condensed phase and the effect of back reaction from ambient gas are taken into consideration. Chemical and isotopic fractionation factors and the Peclet number for evaporation are the three main parameters that control the fractionation. Dust enrichment factor (η), the ratio of the initial dust quantity to that required for attainment of gas-dust equilibrium, is critical when back reactions become significant. Dust does not reach equilibrium with gas at η < 1. Notable chemical and isotopic fractionations usually take place under these conditions. There are two circumstances in which isotopic fractionation of a very volatile element does not accompany chemical fractionation during isothermal heating. One is free evaporation when diffusion in the condensed phase is very slow (η = 0), and the other is evaporation in the presence of ambient gas (η > 0). In the former case, a quasi-steady state in the diffusion boundary layer is maintained for isotopic fractionation but not for chemical fractionation. In the latter case, the back reaction brings the strong isotopic fractionation generated in the earlier stage of evaporation back to a negligibly small value in the later stage before complete evaporation. The model results are applied to cosmochemical fractionation of volatile elements during evaporation from a condensed phase that can be regarded as a binary solution phase. The wide range of potassium depletion without isotopic fractionation in various types of chondrules (Alexander et al., 2000) is explained by instantaneous heating followed by cooling in a closed system with various degrees of dust enrichment (η = 0.001-10) and cooling rates of less than ~5°C/min. The extent of decoupling between isotopic and chemical fractionations of various elements in chondrules and matrix minerals may constrain the time scale and the conditions of heating and cooling processes in the early solar nebula.